Workflows and Outcomes in Patients With Suspected Large Vessel Occlusion Stroke Triaged in Urban and Nonurban Areas. Issue 12 (19th October 2022) - Garcia-Tornel, Alvaro; Millan, Monica; Rubiera, Marta; Bustamante, Alejandro; Requena, Manuel; Dorado, Laura; Olivé-Gadea, Marta; Jiménez, Xavier; Soto, Angels; Querol, Marisol; Hernández-Pérez, Maria; Gomis, Meritxell; et al.
Abstract : Background: We aim to compare the outcome of patients from urban areas, where the referral center is able to perform thrombectomy, with patients from nonurban areas enrolled in the RACECAT trial (Direct Transfer to an Endovascular Center Compared to Transfer to the Closest Stroke Center in Acute Stroke Patients With Suspected Large Vessel Occlusion). Methods: Patients with suspected large vessel occlusion stroke, as evaluated by a Rapid Arterial Occlusion Evaluation score of ≥5, from urban catchment areas of thrombectomy-capable centers during RACECAT trial enrollment period were included in the Stroke Code Registry of Catalonia. Primary outcome was disability at 90 days, as assessed by the shift analysis on the modified Rankin Scale score, in patients with an ischemic stroke. Secondary outcomes included mortality at 90 days, rate of thrombolysis and thrombectomy, time from onset to thrombolysis, and thrombectomy initiation. Propensity score matching was used to assemble a cohort of patients with similar characteristics. Results: The analysis included 1369 patients from nonurban areas and 2502 patients from urban areas. We matched 920 patients with an ischemic stroke from urban areas and nonurban areas based on their propensity scores. Patients with ischemic stroke from nonurban areas had higher degrees of disability at 90 days (median [interquartle range] modified Rankin Scale score, 3 [2–5] versus 3 [1–5], common odds ratio, 1.25 [95% CI, 1.06–1.48]); the observed average effect was only significant in patients with large vessel stroke (common odds ratio, 1.36 [95% CI, 1.08–1.65]). Mortality rate was similar between groups(odds ratio, 1.02 [95% CI, 0.81–1.28]). Patients from nonurban areas had higher odds of receiving thrombolysis (odds ratio, 1.36 [95% CI, 1.16–1.67]), lower odds of receiving thrombectomy(odds ratio, 0.61 [95% CI, 0.51–0.75]), and longer time from stroke onset to thrombolysis (mean difference 38 minutes [95% CI, 25–52]) and thrombectomy(mean difference 66 minutes [95% CI, 37–95]). Conclusions: In Catalonia, Spain, patients with large vessel occlusion stroke triaged in nonurban areas had worse neurological outcomes than patients from urban areas, where the referral center was able to perform thrombectomy. Interventions aimed at improving organizational practices and the development of thrombectomy capabilities in centers located in remote areas should be pursued. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02795962.